The Effects of Supreme Constitutional Court Decision of Unconstitutionality Legislative Omission: A Comparative Study - Aboelazm, Karem (Lex Scientia Law Review, 2025)
This study aims to present the effects of ruling the unconstitutionality of legislative omission and the consequences that result from it. The methods of implementing this type of constitutional ruling by reviewing the role of the executive and judicial authorities in implementing the ruling of unconstitutionality of legislative omission and the role of the Supreme Constitutional Court in setting controls in its ruling that are considered Complementary to the text ruled unconstitutional due to legislative oversight. The study also aims to clarify the extent of the validity of the ruling unconstitutional of the legal text affected by the omission, the role of the legislative authority in activating the legal texts ruled unconstitutional due to legislative oversight, especially if the Supreme Constitutional Court does not establish controls, conditions, or standards that complement This text, and therefore the failure of the legislative authority to intervene will lead to disruption of the implementation of the text. The study relied on two approaches to answer the main question of this study as well as its sub-questions: the comparative approach to compare Egypt, Italy, and Belgium in how to deal with the effects of the ruling of unconstitutionality due to legislative negligence and the content analysis approach to analyze the practices of the Supreme Constitutional Court in setting standards, controls, or conditions that It adds to the article that was ruled unconstitutional, as well as the practices of the trial court if the constitutional judge specified these conditions, or if he did not set it.